Breaking Up the Root of Conflict: Fundamentalism and Radicalism in Social Context - Wahid, Sahid; Barsihannor, Barsihannor; Mahmuddin, Mahmuddin (Journal of Universal Community Empowerment Provision, 2025)
This study critically examines the interrelated phenomena of fundamentalism and radicalism, focusing on their conceptual foundations, socio-political functions, and ambivalent impacts within contemporary Indonesian society. Drawing on a qualitative, literature-based methodology, the research engages religious texts, academic discourse, and socio-political theory to explore how these ideologies emerge in response to structural inequality, moral disorientation, and identity-based exclusion. Rather than reducing fundamentalism and radicalism to extremist threats, the study analyzes them as complex, context-dependent responses to perceived injustice and cultural fragmentation. The findings reveal that both ideologies possess dual potentials: they can foster moral solidarity, community resilience, and ethical critique, yet they also risk producing intolerance, exclusion, and authoritarianism particularly when politicized or absolutized. Root causes such as economic marginalization, epistemic insecurity, and elite manipulation are identified as key drivers of ideological entrenchment. The study concludes by emphasizing the need for nuanced, justice-oriented responses that address the structural conditions underlying ideological radicalization, and calls for future research grounded in lived experience, interdisciplinary analysis, and civic ethics.